Postoperative Oronasal Fistula Formation Following The Furlow and Other Three Palatoplasty Techniques: A Systematic Review and Meta-Analysis - Sari, Felicia Puspita; Satrio, Kenny; Samsarga, Gede Wara (Jurnal Plastik Rekonstruksi, 2024)
Introduction : The technique for repairing a cleft palate depends on the length and width of the palate and the type of cleft palate according to the Veau classification. The most common surgical techniques include the Furlow double opposing Z-plasty, the Bardach palatoplasty, the von Langenbeck palatoplasty, and the V-Y pushback. One of the most frequent complications after cleft palate repair is an oronasal fistula (ONF). This article aimed to compare the risk of postoperative ONF formation following cleft palate repair.Method : We searched for manuscripts involving patients with ONF formation following the Furlow, Bardach, von Langenbeck, and V-Y pushback palatoplasty. Electronic literature searching of the PubMed, Scopus, and Cochrane databases was conducted for the studies published up to November 2022.Result: The meta-analysis used 17 studies, including the analysis of 3,207 repaired cleft palates. The Furlow technique was associated with a statistically lower risk of ONF formation when compared to the von Langenbeck and V-Y pushback techniques (RR=0.06[0.43-0.840],p<0.01 and RR=0.30[0.15-0.62],p<0.01 respectively). There were no statistically significant differences regarding ONF formation between the Furlow technique and the Bardach technique (RR=1.45[0.48-0.43],p=0.51).Conclusion: The Furlow technique is associated with a lower risk of ONF compared to the von Langenbeck and V-Y pushback techniques. There were no statistically significant differences in ONF formation between the Furlow and Bardach techniques.